Emotional arousal as a psychological bridge: how digital stimuli shape hedonic and impulsive consumption - Lady Lady; Cristina Anggrena; Lily Purwianti; Andina Fasha; Ronny Firdiansyah Arief (Manajemen dan Bisnis, 2026)
In the rapidly evolving digital landscape of Indonesia, the psychological mechanisms driving live streaming commerce (LSC) remain conceptually fragmented. This study seeks to bridge this gap by investigating how streamer attractiveness, para-social interaction, and information quality collectively shape consumer behaviors within the Stimulus-Organism-Response (S-O-R) framework. This research utilizes a quantitative design, whereby 273 valid responses from Indonesian consumers were collected via purposive sampling. Data were rigorously analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS 4.0 to validate both direct and mediating effects. The findings reveal that all environmental stimuli significantly drive emotional arousal, which functions as the absolute primary catalyst converting digital engagement into hedonic and impulsive consumption behaviors. Notably, arousal serves as a functional substitute for traditional trust in collectivist markets, representing a massive driver for shopping pleasure. This study advances the S-O-R framework by validating emotional arousal as the critical psychological bridge to spontaneous consumption. Managers should prioritize "relational commerce" by fostering "digital friend" personas to sustain affective resonance in high-velocity digital environments.